The - Julivert, Angels (Barron's, 1992)
Describing the world of spiders, this book shows how these skilful spinners hunt their prey and identies poisonous species. In addition, it reveals unusual facts about spiders which "fly", subterranean builders, and aquatic spiders. The book is designed for young readers